Financial Structure and Stock of Infrastructure, Utilities and Transportation Companies - Mubarok*, Faizul; Ulfarini, Deby (Program Studi Keuangan & Perbankan, Fakultas Ekonomi dan Bisnis, Universitas Komputer Indonesia, 2023)
This study aims to analyze the factors that affect the stock prices of companies in the infrastructure sector. This study utilizes a panel data regression method conducted from 2015 to 2022, using quarterly reports from seven different companies. According to the findings, four elements have a major impact on the stock price. The return on assets (ROA), price to book value (PBV), and total asset turnover (TATO) have a positive impact on stock prices, while debt to equity ratio (DER) has a negative impact. These findings are consistent with previous research on factors that affect stock prices. Companies should pay close attention to consistency in financial ratio indicators that affect stock prices, as demonstrated by this study. Financial ratio volatility is associated with higher risk and lower investor trust. Keywords: Company; Performance; Stock; Infrastructure; Ratio Abstrak Tujuan utama penelitian ini adalah untuk mengidentifikasi faktor-faktor yang berkontribusi terhadap fluktuasi harga saham. Penelitian ini menggunakan metode regresi data panel yang dilakukan dari tahun 2015 sampai dengan 2022, dengan laporan triwulanan dari tujuh perusahaan yang berbeda. Price to book value (PBV), return on assets (ROA), dan total asset turnover (TATO) memiliki pengaruh positif terhadap harga saham, sedangkan debt to equity ratio (DER) memiliki pengaruh negatif. Temuan ini konsisten dengan penelitian sebelumnya mengenai faktor-faktor yang mempengaruhi harga saham. Perusahaan harus memperhatikan konsistensi indikator rasio keuangan yang mempengaruhi harga saham, seperti yang ditunjukkan oleh penelitian ini. Volatilitas rasio keuangan dikaitkan dengan risiko yang lebih tinggi dan kepercayaan investor yang lebih rendah. Kata Kunci: Perusahaan; Kinerja; Saham; Infrastruktur; Rasio